Evidence for Suppression of Onchocerciasis Transmission in Bioko Island, Equatorial Guinea. - Laura Moya; Zaida Herrador; Thuy Huong Ta-Tang; Jose Miguel Rubio; Maria Jesús Perteguer; Ana Hernandez-González; Belén García; Rufino Nguema; Justino Nguema; Policarpo Ncogo; Teresa Garate; Agustín Benito; et al. (Public Library of Science (PLoS), 2016)
Onchocerciasis or "river blindness" is a chronic parasitic neglected tropical disease which is endemic both in mainland and insular Equatorial Guinea. We aim to estimate the current epidemiological situation of onchocerciasis in Bioko Island after vector elimination in 2005 and more than sixteen years of Community Directed Treatment with Ivermectin (CDTI) by using molecular and serological approaches for onchocerciasis diagnosis. A community-based cross-sectional study was carried out in Bioko Island from mid-January to mid-February 2014. A total of 544 study participants were recruited. A complete dermatological examination was performed and three skin snips were performed in every participant for parasitological and molecular assessments. Blood spots were also taken for determination of Ov16 IgG4 antibodies trough an "in-house" ELISA assay. Overall, we found 15 out of 522 individuals suffering any onchocerciasis specific cutaneous lesions and 16 out of 528 (3.0%) with onchocercal nodules in the skin. Nodules were significantly associated with age, being more common in subjects older than 10 years than in younger people (3.9% vs. 0%, p = 0.029). Regarding the onchocerciasis laboratory assessment, no positive parasitological test for microfilaria detection was found in the skin snips. The calculated seroprevalence through IgG4 serology was 7.9%. No children less than 10 years old were found to be positive for this test. Only one case was positive for Onchocerca volvulus (O. volvulus) after skin PCR. The present study points out that the on-going mass ivermectin treatment has been effective in reducing the prevalence of onchocerciasis and corroborates the interruption of transmission in Bioko Island. To our knowledge, this is the first time that accurate information through molecular and serological techniques is generated to estimate the onchocerciasis prevalence in this zone. Sustained support from the national program and appropriate communication and health education strategies to reinforce participation in CDTI activities are essential to ensure progress towards onchocerciasis elimination in the country.